The Implementation of TPACK and Its Impact on EFL Students’ Achievement: A Systematic Literature Review - Siti Aminatuz Zahro; Ive Emaliana; Khairil Azwar Razali; Frida Unsiah; Wan Nurul Elia Haslee Sharil; Rafidah Sahar; Ulfah Sutiyarti (Journal of Pedagogy and Education Science, 2026)
The Systematic Literature Review (SLR) study examines the implementation of TPACK in an EFL context and its impact on EFL students' achievement more broadly in a global context. This SLR study followed the PRISMA and PICOC protocol standards to achieve the research objectives. The data collection stage used the Scopus journal database to obtain credible literature by using Publish or Perish (PoP) software to collect the literature sources. Thirty-two articles from 2016-2025 were obtained, which were then screened and reviewed using Covidence software for relevance to the research topic. The results show that TPACK contributes to developing students' English language skills, a factor that has not been extensively studied and understood by previous research. Therefore, it can be concluded that this study aims to systematically fill the gap in previous research by integrating TPACK into student learning outcomes and includes recommendations for future research to further explore the implementation of TPACK using a larger database and several stakeholder perspectives that were not yet achieved by this study.